RELIGIOUS LIFE OF MUSLIM STUDENT IN NON-ISLAMIC SCHOOL - Rohman, Anas; Lutfiyah, Mar’atul; Achmad, Noor; Ishomi, Zam Zam; Maharani, Khadijah (TAWASUT, 2021)
Abstract Religious life is a real thing happening to the community or community as a form of expression of the belief in religion. The community referred to in this paper is a community of Muslim learners who attend a non-Islamic school. How Muslim life is seen in this non-Islamic school will be seen in this paper. Guided by the two dimensions of Glock and Stark's religious dimensions, the dimensions of religious practice and the dimensions of religious teachings in behavior, make religious life visible in non-Islamic schools. Religious practice is meant worships in muamalah. While the practice of behavior is referred to as the behavior of learners when interacting with the school community. Keywords: Religious life, Muslim students, and Non-Islamic School.